HUBUNGAN ANTARA DUKUNGAN SOSIAL ORANG TUA TERHADAP MOTIVASI BERLATIH ATLET BOLA VOLI PUTRI KLUB TVRI SUMUT TAHUN 2014 - Sukma Mentari Pertiwi (Universitas Negeri Medan, 2015)
This Watchfulness aims to detect connection between parents social support towards motivation practises club daughter volleyball athlete TVRI sumut year 2014. data collecting method uses parents social support scale and motivation scale practises. in this watchfulness is author chooses watchfulness location at volleyball club TVRI sumut. as to that be population in this watchfulness volleyball club daughter athlete TVRI sumut that numbers 40 athletes with 40 person old athletes, so that the population numbers 80 person. so this watchfulness is overall watchfulness (total sampling) with sample total equal to the population total that is 80 person. instrument that used to look for parents social support data and motivation practises club daughter volleyball athlete TVRI sumut with inquiry before worn for watchfulness, inquiry beforehand tested to try at daughter build embryo volleyball club then is looked for validity and reliabilitas inquiry. after looked for validity and reliabilitas inquiry from 40 statement grains obvious found 18 statement grains not valid.Analysis result shows found positive connection between parents social support towards motivation practises club volleyball athlete TVRI sumut year 2014 with correlation value r_xy > r_tabel (0,426 > 0,312) in real standard? = 0,05 that more positiveer parents social support so motivation excelsior practises club volleyball athlete TVRI sumut year 2014. on the contrary more negativeer parents social support so more lower motivation practises club Keyword : Connection Between Parents Social Support and Motivation Practises